Hubungan Meaning of Life dengan Kemandirian Belajar di SMAN 9 Padang di Era New Normal - Riadi, Yunda Salma; Firman, Firman (Current Issues in Counseling, 2022)
This research was motivated by the lack of meaning in students' lives in learning so that they did not have clear goals for the previous period. This can be seen from the existence of students who are less active in the learning process, do not have their own initiative in the learning process, and do not have the desire to do assignments without the help of others. One factor that is thought to influence it is the meaning of life. The aim of this research is to determine the relationship between the meaning of life and students' learning independence in the new normal era. This research approach uses a quantitative approach with a correlational descriptive type. The population of this study were students of SMAN 9 Padang. Data were analyzed using percentage techniques and Pearson Product Moment Correlation. The results of the research are: (1) The overall meaning of student life in the new normal era is generally in the medium category, (2) student learning independence is in the medium category, (3) and there is a very significant relationship between the meaning of life and student learning independence in the new normal era with a correlation of 0.725 which is in the strong category and a significance level of 0.000.